2021
DOI: 10.3390/ijerph182111417
|View full text |Cite
|
Sign up to set email alerts
|

‘I Live a Kind of Shadow Life’: Individual Experiences of COVID-19 Recovery and the Impact on Physical Activity Levels

Abstract: Understanding of strategies to support individuals recovering from coronavirus disease 2019 (COVID-19) is limited. ‘Long COVID’ is a multisystem disease characterised by a range of respiratory, gastrointestinal, cardiovascular, neurological, and musculoskeletal symptoms extending beyond 12 weeks. The aim of this study was to explore individuals’ experiences of recovering from COVID-19 to provide a better understanding of the acute and long-term impact of the disease on physical activity (PA). Individualised se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 14 publications
3
50
0
1
Order By: Relevance
“…Our findings show that participants easily become fatigued while engaging in physical activity, even during treatment. These findings are consistent with Shelley et al’s study of individuals with persistent COVID-19 symptoms [ 44 ]. Participants in that study reported that COVID-19 had a profound impact on all aspects of their lives and made them inactive compared to their pre-COVID-19 status [ 44 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings show that participants easily become fatigued while engaging in physical activity, even during treatment. These findings are consistent with Shelley et al’s study of individuals with persistent COVID-19 symptoms [ 44 ]. Participants in that study reported that COVID-19 had a profound impact on all aspects of their lives and made them inactive compared to their pre-COVID-19 status [ 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with Shelley et al’s study of individuals with persistent COVID-19 symptoms [ 44 ]. Participants in that study reported that COVID-19 had a profound impact on all aspects of their lives and made them inactive compared to their pre-COVID-19 status [ 44 ]. Moreover, another study found that persistent symptoms adversely affected people’s ability to engage in exercise, job duties, self-care, and housework, mostly by making them tired [ 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…As a matter of fact, current data point out that COVID-19 survivors experience at least one limitation with daily life activities [ 17 ]. Among these limitations, difficulties with mobility (such as walking, climbing stairs, or lifting weights [ 17 , 18 , 19 ]) and limitations in living alone without assistance [ 20 ], as well as in returning to daily social and work activities [ 17 , 20 , 21 ], were observed. However, the real impact of brain-related sequelae of COVID-19 on disability levels has not been systematically addressed.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 , 10 Yet recovery prognostics and optimum standards of rehabilitation are less clear. 11 , 12 Further, their pathway to survival and recovery as well as their access to health care has, and will be, altered by social distancing measures and additional pressures on health and social care during and after the pandemic. 13 Experiences of illness, survival and recovery for those admitted to intensive care units with COVID‐19 will include unique challenges compared to those who have survived critical illness prior to the pandemic.…”
Section: Introductionmentioning
confidence: 99%